2019
DOI: 10.3390/molecules24224023
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Determination in Natural Zeolites by Thermal Decomposition Atomic Absorption Spectrometry: Method Validation in Compliance with Requirements for Use as Dietary Supplements

Abstract: Natural zeolites are hydrated aluminosilicate minerals that, due to their remarkable physical-chemical properties of being molecular sieves and cation exchangers, have applications in different areas such as environmental protection, catalysis, animal feed, and dietary supplements. Since natural zeolites may contain traces of undesirable compounds such as toxic metals, the accurate quantification of these elements is necessary. In this study, a direct method for Hg determination in zeolite samples based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
(38 reference statements)
0
16
1
Order By: Relevance
“…A possible explanation could be the purification effect of HCl by solubilization of mineral impurities from the quartz crystal lattice structure [26,28]. Arcoya et al reported a decrease of the characteristic peaks by HCl treatment, however our results show no modification of the characteristic peak intensities, probably due to the stability of crystal structure [26,29]. Our results are in line with those of Kavak et al, who reported that the characteristic peak intensities of clinoptilolite in the control sample were nearly the same as those of samples exposed to gastric fluids [19].…”
Section: Structure Of the Zeolitescontrasting
confidence: 78%
See 1 more Smart Citation
“…A possible explanation could be the purification effect of HCl by solubilization of mineral impurities from the quartz crystal lattice structure [26,28]. Arcoya et al reported a decrease of the characteristic peaks by HCl treatment, however our results show no modification of the characteristic peak intensities, probably due to the stability of crystal structure [26,29]. Our results are in line with those of Kavak et al, who reported that the characteristic peak intensities of clinoptilolite in the control sample were nearly the same as those of samples exposed to gastric fluids [19].…”
Section: Structure Of the Zeolitescontrasting
confidence: 78%
“…The contents of Al, Fe, Ca, Mg, K, Na, Mn, and Ti in RZ and TZ samples were determined using a S1 Titan 800 X-ray fluorescence spectrometer (Bruker, Berlin, Germany). The conversion to the corresponding oxide was made by multiplying the element concentration with 1.8895 (Al 2 O 3 ), 1.4297 (Fe 2 O 3 ), 1.3392 (CaO), 1.6583 (MgO), 1.2046 (K 2 O), 1.3480 (Na 2 O), 1.2912 (MnO), and 1.6683 (TiO 2 ) [29]. The SiO 2 and loss of ignition (LOI) were determined by gravimetry [38].…”
Section: Characterizationmentioning
confidence: 99%
“…Microwave digestion of a 0.5 g powder of sample using microwave-assisted acid digestion using a microwave system (Berghof, Eningen, Germany) was described elsewhere [31]. The heating program of the microwave system for samples digestion comprised three steps of heating at 160 • C, 200 • C, the cooling at 100 • C, in a total time of digestion of 35 min.…”
Section: Instrumentation and Methodsmentioning
confidence: 99%
“…Beside these, other non-conventional techniques can also be used to determine metal analytes in different samples [28][29][30]. For specific elements (i.e., Hg) which have high volatility, the direct measurement in solid samples (including zeolites) by thermal desorption is possible [31].…”
Section: Introductionmentioning
confidence: 99%
“…The direct determination of chemical vapor-generating elements by avoiding derivatization was also attempted. Therefore, mercury determination by thermal decomposition atomic absorption spectrometry (TD-AAS) [ 37 , 38 ], liquid/solid sampling with electrothermal vaporization (ETV) in GFAAS [ 39 , 40 , 41 ], or the emergent HR-CS-ETAAS using Xe lamp [ 42 , 43 ] were successfully applied. At the same time, ICP OES [ 44 ] and ICP-MS [ 45 , 46 ] using pneumatic and ultrasonic nebulization, or solid sampling by laser ablation (LA-ICP-MS) [ 47 ] and LIBS OES [ 48 ] provide simultaneous direct determination without derivatization.…”
Section: Introductionmentioning
confidence: 99%